Moderasi Beragama: Upaya Revitalisasi Nilai-Nilai Pancasila Perspektif Al-Qur’an - Muhammad Haris Suwandi Pratama,; M. Yusuf Qardawi,; Iskandar, (Tasamuh: Jurnal Studi Islam, 2024)
This paper aims to assert that moderation is an effort to revitalize the values of Pancasila from the perspective of the Qur'an. This research is a literature research using thematic interpretation approach (maudhu'i). Comprehensively, this paper examines: 1) How is the concept of moderation? 2) How is the urgency of moderation? and 3) How is moderation implemented? The results of this study show that: 1) Moderation is a way of seeing, thinking, and acting to take the middle way (by using the principles of moderation) against excessive religious understanding and expression. 2) Moderation is considered urgent because it is a solution to radical isms. 3) Moderation is implemented to foster spiritual values, humanism, nationalism, democracy, and integrity.